Off the mark : how grades, ratings, and rankings undermine learning (but don't have to) - Schneider, Jack (Writer on education); Hutt, Ethan L. (Harvard University Press, 2023)
"Today's regimes of testing and grading satisfy only the politicians who forced them on America's schools. Yet discarding assessment also serves students poorly. Off the Mark proposes an alternative, replacing motivation-killing tests and grading systems with well-designed assessment that accurately captures learning and fosters students' potential"--